The Problem of an orthotropic round plate under the action of the surface tangential loadings taking into account the transversal shear - R. M. Kirakosyan; S. P. Stepanyan (National Academy of Sciences of Armenia)
An asymptotic problem of bend of an orthotropic round plate of constant thickness which is under the action of radially directed surface tangential loadings is, considered. The Problem is solved with the application of shear theory of the first arider. For the maximum bend the coefficient of corrections is calculated. Рассмотрена осесимметричная задача изгиба ортотропной круглой пластинки постоянной толщины, которая находится под действием радиально направленных поверхностных касательных нагрузок. Задача решена с применением сдвиговой теории первого порядка. Для максимального прогиба рассчитан коэффициент поправок.
Keywords: Physics